Polymorphism of the THOC5 of the transcription/export multiprotein complex and its correlation with the lipid and metabolic profile in middle-aged women. (3rd March 2020) - Loja-Chango, Rita; Salazar-Pousada, Danny; Escobar-Valdivieso, Gustavo S.; Ramírez-Morán, Cecibel; Espinoza-Caicedo, Jasson; Pérez-López, Faustino R.; Gavilanes, Antonio W. D.; Chedraui, Peter
Abstract: The transcription/export complex (TREX) is formed by a core called THO. These are necessary for the transcription and packaging of messenger RNA and its subsequent nuclear exportation. Studies have correlated THO-specific polymorphisms with abnormalities of HDL-C metabolism. To correlate lipid and metabolic parameters with the genetic variants of the rs8135828 polymorphism of the THOC5 gene in middle-aged women. DNA was extracted from the whole blood of 183 women aged 40–65 and tested for the rs8135828 polymorphism of the THOC5 gene using real-time PCR. HDL-C, LDL-C, triglyceride, and total cholesterol levels, as well as other metabolic parameters, were correlated with the polymorphism genotypes: GG, AG, and AA. Mean age of women was 50.6 ± 6.3 years, 54.6% were postmenopausal and 16.4% had the metabolic syndrome. GG was the most frequently determined genotype (62.3%). There were no differences in lipid levels according to genotypes; although there was a trend for lower HDL-C levels for the AA and AG + AA genotypes. Those with the AG and AG + AA genotypes displayed significantly higher glucose levels ( p  = .02 and p  = .002, respectively); with a trend toward a higher metabolic syndrome prevalence and increased abdominal perimeters in both variants (AG and AG + AA). The AG genotype was related to higher glucose levels but not with abnormal lipid parameters. There is a need for more research in this regard.